Scaled models in the analysis of fire-structure interaction. (October 2015) - Andreozzi, A; Bianco, N; Musto, M; Rotondo, G
Abstract: A fire problem has been scaled both in terms of geometry, boundary conditions and materials thermophysical properties by means of dimensionless parameters. Both the full and scaled models have been solved numerically for two different fire power values. Results obtained by means of the full scale model and the scaled one are compared in terms of velocity and temperature profiles in order to assess the reliability of the scaled model to represent the behavior of the full scale one.